PEMBENTUKANJIWA WIRAUSAHA DI DUSUN CANDRAN MELALUIPELATIHAN PEMBUATAN DAN PEMASARAN KRIPIK BONGGOL PISANG - Jamalul Lail (UII, 2014)
Indonesia as a country with great potential resources should have a number ofentrepreneurs are numerous. But in fact the number of entrepreneurs in Indonesia doesnot reach 1% of the total population density. This is because people generally do notwant to be entrepreneurs because of a big risk and minimal knowledge. As happened inthe dusun CandranSentono village, Klaten , Central Java,where villagers are so rare thatbecome entrepreneurs. The potential resources are plentiful enough in the dusunCandran one banana hump that can be used as a product that has a pretty goodeconomic value if managed and marketed well. Under these conditions, the creation ofnew programs held in the hamlet of entrepreneurial spirit through training Candranchips manufacture and marketing of banana hump. Through the training of citizens canunderstand how to cultivate and exploit the natural resources around the existing onebanana hump that can be used as chips economic value and can learn how to packageand market the product well. The training also improve the morale of citizens forentrepreneurship by utilizing available resources.